2020
DOI: 10.5194/aab-63-315-2020
|View full text |Cite
|
Sign up to set email alerts
|

Determination of genetic variation within the <i>DYRK2</i> gene and its associations with milk traits in cattle

Abstract: Abstract. To speed up the progress of marker-assisted selection (MAS) in cattle breeding, the dual-specificity tyrosine phosphorylation-regulated kinase 2 (DYRK2), cadherin 2 (CDH2), and kinesin family member 1A (KIF1A) genes were chosen based on our pervious genome-wide association study (GWAS) analysis results. DYRK2 is a kinase that may participate in cell growth and/or development; it shows phosphorylation activity toward serine, threonine, and tyrosine fragments of proteins, and it is different from other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…OSMR gene was discovered as a candidate gene in innate immunity in dairy sheep [92], also the potential role of this gene was determined in resistance to udder infection in dairy cattle [93]. The DYRK2 gene was associated with milk traits in cattle [94]. Single nucleotide polymorphisms (SNPs) studies in crossbred Bos indicus-Bos taurus cows indicated that this gene has been documented with some role in mammary development [95].…”
Section: Discussionmentioning
confidence: 99%
“…OSMR gene was discovered as a candidate gene in innate immunity in dairy sheep [92], also the potential role of this gene was determined in resistance to udder infection in dairy cattle [93]. The DYRK2 gene was associated with milk traits in cattle [94]. Single nucleotide polymorphisms (SNPs) studies in crossbred Bos indicus-Bos taurus cows indicated that this gene has been documented with some role in mammary development [95].…”
Section: Discussionmentioning
confidence: 99%